Nostalgia increases financial risk taking - Zou, Xi (2020)
We examined, in five studies, the relation between nostalgia and financial risk taking. We hypothesized that nostalgia increases risk taking by fostering perceptions of social support. In Study 1, we established the basic effect of nostalgia and increased risk taking. In Study 2, we used a measurement-of-mediation approach to specify the underlying mechanism. Perceived support from family members, rather than from significant others or friends, mediated the relation between nostalgia and risk taking. In Studies 3 to 4, we further specified the mediating mechanism (i.e., family social support) and established direction of causality by using an experimental-causal-chain approach. Finally, in Study 5, we provided direct experimental evidence of the full mediation model. Taken together, nostalgia galvanizes perceived family support, which propels individuals toward financial risk.